Water and slope stability – the application of a new science - Beale, G (Slope 2013: 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
The science of pit slope hydrogeology has rapidly gained momentum over the past 15 years to meet the requirements of larger and deeper mining projects. The advent of new monitoring systems, and particularly the use of grouted-in vibrating wire piezometers, has contributed to a practical understanding of the factors that control the behaviour of water pressure in pit slopes. An expanding global database linking pore pressure with deformation and slope movement is highlighting the role that water pressure plays in slope stability. The talk discusses the importance of water for slope stability, the integration of geotechnical and hydrogeological studies, and the development of a practical approach for project planning, implementation and monitoring.